Perceptions of Accountants and Finance Managers on the Use of XBRL in Financial Reporting - Lasmiatun, KMT; Hardiwinoto, Hardiwinoto (Westscience Press, 2025)
This study explores the perceptions of accountants and finance managers regarding the adoption of eXtensible Business Reporting Language (XBRL) in financial reporting within the Indonesian context. Using a qualitative approach, data were collected from five informants and analyzed using NVivo software. The findings reveal that XBRL significantly enhances efficiency, accuracy, and compliance in financial reporting. However, challenges such as technical complexity, high implementation costs, and resistance to change hinder its adoption, particularly among smaller organizations. The study highlights the importance of management support, tailored training programs, and government initiatives to promote XBRL adoption. These insights contribute to a deeper understanding of how digital technologies can transform financial reporting practices, offering practical recommendations for overcoming adoption barriers.